Overview of clinical practice guideline development, application to pharmacy practice, and roles for pharmacists. Issue 1 (13th December 2022) - Dixon, Dave L.; Harris, Ila M.; Aljadeed, Raniah; Anderson, Keri C.; Aycock, Anna; Beavers, Craig; Beckman, Elizabeth J.; Isaacs, Diana; McCoy, Emily; Sandler, Anna; Saseen, Joseph J.; Singh, Shivali; et al.
Abstract: All health care professionals have a responsibility to integrate current evidence‐based medicine into their clinical practice to ensure the best possible patient care. Clinical practice guidelines (CPGs) play a major role in helping clinicians identify when and how to implement evidence into routine clinical practice to improve patient outcomes. The primary intent of CPGs is to benefit patients by improving the quality of care; however, CPGs also improve efficiency and effectiveness within the health care system. The process used to develop CPGs is important to ensure the recommendations are trustworthy, based on the highest‐quality evidence, and free of significant conflicts of interest. The National Academy of Medicine (NAM) published guidance on best practices for developing CPGs in 1990 and again in 2011. Additional guidance is provided by various reporting checklists for CPGs, such as the Appraisal of Guidelines for Research & Evaluation (AGREE) II and Reporting Items for Practice Guidelines in Healthcare (RIGHT) instruments. However, analyses of published CPGs show inconsistent application of these best practices. This paper discusses the benefits of CPGs, reviews the guideline development process, discusses limitations in this process and in applying CPGs to patient care, identifies opportunities for improvement, provides considerations for educating learners and other health care professionals about CPGs, and examines the role of pharmacists in CPG development, dissemination, and implementation.